KEMAMPUAN BERPIKIR KRITIS MATEMATIS DAN KECEMASAN MATEMATIKA DALAM PEMBELAJARAN DENGAN PENDEKATAN PROBLEM SOLVING (Studi Eksperimen Pada Kelas X Man Rukoh Kota Banda Aceh) - Mutia Fariha (Jurnal Peluang, 2012)
Abstract Implementation problem solving as an approach in teaching mathematics besides aiming to improve problem-solving skills can also improve students' critical thinking mathematically. In practice, the application of problem solving approach could be expected to cause change math anxiety. Mathematics anxiety is high or too low will affect the ability of critical thinking mathematically. This research is a quantitative approach to experiment with the aim to obtain a picture of increasing mathematical and critical thinking skills of mathematics anxiety of students in learning by using a problem solving approach is reviewed by the entire student and student grouping. This study uses a form of pretest-posttest control group. Collecting data using a test for mathematical and critical thinking skills questionnaire for math anxiety. Based on the analysis concluded that the increase in critical thinking skills that are taught to students' mathematical problem solving approach is higher than the increase in students' critical thinking skills being taught mathematical with conventional approaches based on the students' overall well-reviewed and reviewed based on grouping students. For math anxiety, there are no significant changes between mathematics anxiety before treatment and after treatment both in classes taught by the problem solving approach and the class is taught by conventional approaches. Based on univariate analysis concluded that there was an interaction between these factors and grouping students learning approach to improving the ability to think mathematically ktitis or math anxiety.Keywords: mathematical critical thinking skills, math anxiety, problem solving approach